Analysis of single nucleotide polymorphisms with opposite effects on serum iron parameters in South African patients with multiple sclerosis - Moremi, Kelebogile Elizabeth (Stellenbosch : Stellenbosch University, 2014)
Thesis (MMed)--Stellenbosch University, 2014.